Efek Latihan Super Garuda Shield terhadap Kepentingan Nasional Indonesia - Rusydi, Muhammad Raditya; Radhiansyah , Emil (Jurnal Keamanan Nasional, 2024)
National interest has becoming an important goal of state in every action it takes. Military cooperation is one of the state effort to gain it interest in order to give response to the change of security matters nationally, regional and international. Military combined exercise has becoming one of state interest in showing and  increasing its military capabiity and superiority. Super Garuda Shield as Indonesia’s strategy to achieve its national interest in the field of defence. This article is try to understand and point out Indonesia’s national interest through combined exercise with United States military and rest of Southeast Asian Countries. Thus, through neoralism approach of national interest of Wolfley concept of rehearsal, capacity building, trut developing and Deterrence, indonesia’s national interest is trying to analys. In order to gain a general and specific picture of the exercise, literature review and interview with academician and think thank analyst who understand on the event was did. The conclucion to the analysis is that the understanding the Indonesia’s motivation to gain an acknowledgement of its military capability increasement as well as to calculate Indonesia preparadness to the coordination of its military branches in order to perform its military professionalism in the region.